Analisis Bibliometrik Digital Marketing Publikasi Ilmiah di Negara-Negara Seluruh Dunia - Indah Karunia Sari; M Ruslianor Maika (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study is to measure the development of scientific publications related to "digital marketing". While the benefits of this study is to determine the effect on increasing sales volume. In this study, researchers collected data obtained from the Scopus database using the keyword "digital marketing". The research method used by the researcher is descriptive quantitative method with bibliometric analysis. Based on data searches, researchers obtained 12,401 scientific work search documents which were then exported in BibTex format and processed using R-Packages software and Biblioshiny Webinterface. This is of course very helpful as a reference for research literature on various economics carried out in the future. Keywords: Bibliometric Analysis, Digital Marketing, Digital Marketing